Responsiveness and Tangible of Leave and Permit Services for Civil Servant of Tolitoli Regency - Iqbal, Muhammad; Nursifa, Nursifa; Makmur, Syarif; Gafar, Masrin; Basir, Umar (Perkembangan Kajian Sosial, 2025)
This study aims to determine the responsiveness and tangible of leave and permit services for Pegawai Negeri Sipil (PNS) at the Badan Kepegawaian dan Pengembangan Sumber Daya Manusia (BKPSDM) of Tolitoli Regency. This research uses a qualitative descriptive approach, The study was conducted from November 2022 to January 2023 through observation, interviews with seven informants selected by purposive sampling, and documentation studies. Data analysis used the Miles, Huberman and Saldana model. The study results indicate that the responsiveness dimension still needs to be improved. Although officers are friendly and follow procedures, service responses are obstructed by long disposition paths, high workloads, and suboptimal communication systems. Limited implementers, lack of socialization, and the absence of authorized officials also worsen the response. Meanwhile, the tangible dimension (direct evidence) shows limited physical facilities, such as inadequate waiting rooms and only one computer available. Manual procedures and minimal visual information also slow down services and affect applicant satisfaction.